The effect of ligation of the distal vein in snuff-box arteriovenous fistula - Beigi Ali; Masoudpour Hassan; Alavi Maryam (Saudi Journal of Kidney Diseases and Transplantation, 2009)
Arterio-venous fistula (AVF) in the snuff-box region is one of the current techniques used for creating a vascular access in patients undergoing dialysis. The aim of this study is to find out whether ligating the distal vein in AVF in the snuff-box will bring about any change in the efficiency and complications of the fistula. Sixty patients (30 males, 30 females) suffering from chronic renal failure, who had been admitted for creating an AVF, were randomly divided into two groups after having filled out consent forms. After the AVF was made, the distal vein was ligated in the first group, but not in the second group. The patients were discharged after being given the necessary advice on how to take care of their fistula. They were examined on post-surgical days 1, 30 and 90. Early efficiency in the ligated and non-ligated groups was 100% and 96.7% respectively while late efficiency in the two groups was 90% and 83.4%, respectively (P > 0.05). The most common complication in both groups was thrombosis (11.7%). Venous hypertension and edema were observed in two patients (both from the non-ligated group) and infection of the surgical site was observed in only one patient. Our study suggests that, considering the high efficiency level and low complication rate, AVF at the snuff-box region constitutes one of the best possible vascular accesses for patients undergoing hemodialysis. Ligation of the distal vein prevents the development of venous hypertension in the fistula.